INSTALASI PATUNG GANESHA DAN PAHAM SIVAISME DI BALI - Mudana, I Gede Raka (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
One ofe the sculpture that began to develop in some modern Hindu homes is the placement of the statue of the god Ganesha. The placement of the Ganesha idol is adjusted to the intent and purpose of Hindus in Bali. This also indirectly shows the variety and omnipotence of the god Ganesha. The trend of placing the statue of the god Ganesha and worshiping the god Ganesha in Bali further adds to the lively Hindu religious practices in Bali. Then the statue of Ganesha is not feasible to be placed in the house because it is a manifestation of Shiva, the main deity in Hindu mythology of Hinduism, the god Ganesha is a god who has a holy nature. Whereas in the Balinese Hindu school based on Buddhist Shiva which is manifested in three forces called Tri Sakti or Tri Murti, and in practice it is thick with Bhairawa rulers who already have standardized rules and are hereditary in Bali. Because Hinduism in Bali breathes Shiva Bhairawa, namely worship of god (Shiva God) in the form of his magic that is Dewi Uma or Goddess Durga.Â